LOGICAL REASONING ANALYSIS BASED ON HIPPOCRATES PERSONALITY TYPES - Nurdin, Nurdin; Samad, Ita Sarmita; Sardia, Sardia (Aksioma, 2020)
Abstract: The theory distinguishes human based on four different personality types such as: sanguine, choleric, melancholic, and phlegmatic. Different types of personality caused by differences in the dominant fluid in the body. These differences will result in terms of behavior, ways of thinking and to get along. The type of this research that is descriptive qualitative which it is describing the logical reasoning based on Hippocrates personality types. The logical reasoning is analyzed through the four types of personality in relation to mathematical problem solving. The Analysis is done based on the logical reasoning indicator/ subindicator and the steps of problem solving stated by Polya. The result shows that there is a reasoning difference on each type of personalities. The difference can be terms of the strenght or the weakness. Sanguine is quicker in understanding problems and communicating results, choleric is more accelerated in work, melancholic is more perfect at work, and phlegmatic is superior in terms of accuracy. Keywords: Logical reasoning, Hippocrates, sanguine, choleric, melancholic, phlegmatic